Land settlement and degradation: dynamics of land use in recently settled forest areas of Kerala - Velluva, Sanathanan (New Delhi, 2006)
Land settlement and degradation in the marginal lands, especially in the mountain slopes are among the most discussed subjects among researchers both nationally and internationally. The immediate consequence of such settlement is deforestation though resource acquisition in large scale and indiscriminate use of such resources for immediate benefits. This book analyses the changes in the land use in one of the fragile parts of Kerala State owing to massive settlement of people from the plain land mainly to acquire land. In the land hunt strategy of non tribals, they encroach upon land which belongs to the tribes people without recognising the latter's legitimate rights. Therefore, the original forest dwellers lost not only their cultivable land but also their accessibility to many livelihood resources. The land use scenario has undergone spectacular changes owing to the entry of an array of cultivation practices. A large portion of the forest areas turned into agricultural land and a vast majority of the greenery turned into barren land. The indigenous tribal cultivation ruined and in its place a new form of cropping pattern emerged. The socio economic settings of the tribes people now pose a severe setback as their sustainable dependency has been questioned by variety of land use dynamics. In order to arrest further degradation and to maintain a balanced land use system one should have a deep insight into dynamics of land use in the process of in-migration. Thus, the book focuses on the process of settlement, land alienation, the genesis of degradation and process of crop succession in one of the most fragile tribal areas of Kerala.
Keywords: Land use